Prognostic value of sarcopenia in patients with unresectable colorectal liver metastases after drug-eluting beads transcatheter arterial chemoembolization: a single center retrospective study - Fuquan Wang; Bingxin Gong; Lei Chen; Yanyan Cao; Licheng Zhu; Bin Chai; Jihua Wang; Guofeng Zhou; Chuansheng Zheng (Scientific Reports)
Abstract Sarcopenia is a prevalent condition in tumor patients and can potentially impact the prognosis of tumor treatment. This retrospective study aimed to evaluate the correlations between sarcopenia and the prognosis of patients with unresectable colorectal liver metastases (CRLM) received drug-eluting beads transcatheter arterial chemoembolization (DEB-TACE) therapy. From December 2018 to December 2023, unresectable CRLM patients who had already received second-line therapy from the Wuhan Union Hospital were involved in our study. Skeletal muscle mass was evaluated on CT at the L3 vertebra, and the optimal cut-off point for skeletal muscle index classification was determined using x-tile software. Overall survival (OS) and progression-free survival (PFS) were estimated using Kaplan–Meier analysis and Cox regression analysis. Seventy-one patients were included in the study, 34 with sarcopenia (sarcopenia group) and 37 without sarcopenia (non-sarcopenia group), respectively. The median PFS and OS was elevated in the non-sarcopenia group compared with the sarcopenia group (6.1 months versus 4.3 months, p = 0.012; 14.8 months versus 10.2 months, p < 0.001). The multivariate Cox regression analysis revealed that sarcopenia, extrahepatic metastases, and neutrophil-to-lymphocyte ratio (NLR) ≥ 5 were identified as independent risk factors for both PFS and OS. The advantages of non-sarcopenia in terms of OS were consistent across all subgroups examined. Additionally, the sarcopenia group exhibited a higher incidence of vomiting/nausea, fatigue, and abdominal pain following the DEB-TACE operation compared to the non-sarcopenia group. Sarcopenia demonstrated a substantial predictive value for both PFS and OS in unresectable CRLM patients who underwent DEB-TACE treatments. Besides, NLR > 5 and extrahepatic metastases were independent risk factors linked to a poorer prognosis. Furthermore, patients with sarcopenia may face an increased likelihood of experiencing adverse events following DEB-TACE treatments.